2022
DOI: 10.1001/jama.2022.5050
|View full text |Cite
|
Sign up to set email alerts
|

Single Ascending Dose Study of a Short Interfering RNA Targeting Lipoprotein(a) Production in Individuals With Elevated Plasma Lipoprotein(a) Levels

Abstract: ImportanceLipoprotein(a) (Lp[a]) is an important risk factor for atherothrombotic cardiovascular disease and aortic stenosis, for which there are no treatments approved by regulatory authorities.ObjectivesTo assess adverse events and tolerability of a short interfering RNA (siRNA) designed to reduce hepatic production of apolipoprotein(a) and to assess associated changes in plasma concentrations of Lp(a) at different doses.Design, Setting, and ParticipantsA single ascending dose study of SLN360, an siRNA targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
136
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 189 publications
(142 citation statements)
references
References 16 publications
3
136
0
3
Order By: Relevance
“…Plasma Lp(a) levels were reduced by 46% at a dose of 30 mg, 86% at 100 mg, 96% at 300 mg, and 98% at 600 mg, as compared with the 10% with the placebo. Low-grade injection site reactions and headache were common treatment-emergent adverse events [ 119 ].…”
Section: Lipoprotein(a) Lowering Agentsmentioning
confidence: 99%
“…Plasma Lp(a) levels were reduced by 46% at a dose of 30 mg, 86% at 100 mg, 96% at 300 mg, and 98% at 600 mg, as compared with the 10% with the placebo. Low-grade injection site reactions and headache were common treatment-emergent adverse events [ 119 ].…”
Section: Lipoprotein(a) Lowering Agentsmentioning
confidence: 99%
“…The phase I trial of another siRNA molecule olpasiran showed a reduction in Lp(a) for over 90% and very few adverse effects compared with a reduction of up to 80% with pelacarsen in a phase II trial [ 46 , 47 ]. In a small phase I trial of the siRNA SLN360, which enrolled 32 participants with elevated Lp(a) levels and no known CVD, the maximal median percentage change from baseline in Lp(a) level over 150 days was observed: −10%, −46%, −86%, −96%, and −98% for the placebo group and the 30-mg, 100-mg, 300-mg, and 600-mg SLN360 groups, respectively [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…More recently, siRNA targeting LPA mRNA was trialed in a small study ( n = 32). A single dose of siRNA SLN360 was given to increase its selective uptake and concentration within hepatocytes, binding and degrading the apo(a) mRNA and reducing overall Lp(a) plasma levels for 150 days ( 30 ). With studies such as these highlighting the urgent need for Lp(a)-specific therapies, the current guidelines must still focus on managing and mitigating the risk associated with high Lp(a) levels prior to the need for intervention until a specific therapy is widely available ( 7 , 8 , 31 ).…”
Section: Discussionmentioning
confidence: 99%